The Radiance of Dawn (Part-2) - Hamid Hasan Bilgrami, Syed, Dr.; Tranlated By Hassan Akhtar (Lahore Ferozsons (Pvt.) Ltd., 2002)
This book consists of thirteen remaining letters which deals with the basic priniples that should be understood by our graduate and post-graduate students.
Keywords: Islamic -- Concepts